(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The article analyzes the current problems in the field of interethnic and interfaith relations, investigates the dynamics of inter-ethnic relations, evaluates the ethnic policy, identifies the factors of ethnic tensions, conducts sociological analysis of the stability of society based on the expert analysis and various indices and indicators. The paper also covers the main aspects of the model of inter-ethnic harmony in the Republic of Kazakhstan. The authors focuses on the fact that inter-ethnic harmony is a main priority of the state policy and the fundamental value of the Kazakhstani society. This important asset of the Kazakhstani society, which is an essential and integral part of the history of young independent state, established due to the effective activity of central and local government bodies, as well as the Assembly of the People of Kazakhstan and a number of other factors.